BIOGRAFI MARCO KARTODIKROMO SEBAGAI SUMBER BELAJAR SEJARAH - Safitri, Dwi; Arrazaq, Naufal Raffi; Tasnur, Irvan (Universitas Negeri Gorontalo, 2024)
The purpose of writing this article is to analyze the potential of Marco Kartodikromo's biography as a source of historical learning. Marco Kartodikromo is a journalist, writer, and activist who fought for the Indonesian nation against the Dutch colonialists. Marco Kartodikromo has national values that can be learned by the younger generations. These values can be taught in history subject. Educators can integrate Marco Kartodikromo's history in history learning. Marco Kartodikromo fought during the Dutch Colonial Government. The background of this time became the basis for determining historical learning materials related to the biography of Marco Kartodikromo as a source of historical learning.